DETERMINAN PERSISTENSI LABA DENGAN KEPEMILIKAN MANAJERIAL SEBAGAI PEMODERASI - Devi Rianti Marpaung; Amanah Hijriah; Ira Grania Mustika (Journal of Economic, Bussines and Accounting (COSTING), 2025)
Profit is a crucial factor for investors when making investment decisions. It is important for a company to have high-quality or persistent earnings, as these can indicate future profitability. This study aims to analyze the influence of firm size, debt level, and cash flow volatility on earnings persistence, with managerial ownership serving as a moderating variable. The population used in this study consists of 10 banking companies included in the PRIMBANK10 index and listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The entire population was used as the sample, resulting in 40 data observations. This research employs a quantitative approach. The tests used include panel data regression analysis and moderated regression analysis, conducted using EViews 12. The results of the study show that firm size has a significant effect on earnings persistence. Meanwhile, debt level and cash flow volatility do not affect earnings persistence, and managerial ownership as a moderating variable does not strengthen the relationship between firm size, debt level, and cash flow volatility on earnings persistence.